A comparative study of ovulation induction with clomiphene versus clomiphene and bromocriptine in follicular phase of normoprolactinemic PCOS women - Gayathri, S. R.; Tripathy, Saswati; Muthulakshmi, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypothalamic pituitary axis dysfunction accounts for majority of ovulatory disorders and a predominant cause of women with PCOS. There is a dopaminergic control on gonadotropin secretion. In normoprolactinemic PCOS patients transient rise in serum prolactin can be observed during the late follicular phase and luteal phase. So, the aim of the study is to know the effect of bromocriptine and clomiphene in ovulation induction as compared to clomiphene alone. Methods: Based on the various inclusion and exclusion criteria, seventy patients were randomly assigned into two groups. The patients in the first group were treated with tablet of clomiphene citrate (100 mg) from day 3 to day 7 of each cycle. The patients in the other group received 100mg of clomiphene citrate from day 3 to day 7 of each cycle and tablet bromocriptine (2.5 mg) from day5 to day14. Both groups were followed up with follicular study for three months. At the end of the three cycles the hormonal statuses of the patients were determined. Results: There was no significant difference found in other hormones like serum FSH, LH and estradiol in both groups. The follicular diameter and the average endometrial thickness was increased to a significant level in the CC+Bcrt group as compared to the CC group. The rate of ovulation and pregnancy rate was higher in combination group. Conclusions: Bromocriptine with clomiphene in follicular phase has an advantage of improving follicular diameter, endometrial thickness and hence ovulation and pregnancy rates.